Political Parties and Environmental Ethics: The Case of the Dutch Party for the Animals - Otten, Ruud; Gremmen, Baart (ETHICS IN PROGRESS, 2016)
The Dutch Partij voor de Dieren (Party for the Animals), the only political party devoted to animals in the world, wants to take wild as well as domestic animals under its wing and, hence, to remove the traditional dividing line between both domains. How can the Animal Party at the same time claim to stand up for the interests of animals as individuals as well as for the particular interests of wild animals? Rather than perceiving wild animals as mere components of wider entities, the Animal Party starts to personalize wild animals at the moment that their wellbeing can be detected and actively improved.